Boosting the Electrical Double‐Layer Capacitance of Graphene by Self‐Doped Defects through Ball‐Milling. (10th April 2019) - Dong, Yue; Zhang, Su; Du, Xian; Hong, Song; Zhao, Shengna; Chen, Yaxin; Chen, Xiaohong; Song, Huaihe
Abstract: Improving the capacitance of carbon materials for supercapacitors without sacrificing their rate performance, especially volumetric capacitance at high mass loadings, is a big challenge because of the limited assessable surface area and sluggish electrochemical kinetics of the pseudocapacitive reactions. Here, it is demonstrated that "self‐doping" defects in carbon materials can contribute to additional capacitance with an electrical double‐layer behavior, thus promoting a significant increase in the specific capacitance. As an exemplification, a novel defect‐enriched graphene block with a low specific surface area of 29.7 m 2 g −1 and high packing density of 0.917 g cm −3 performs high gravimetric, volumetric, and areal capacitances of 235 F g −1, 215 F cm −3, and 3.95 F cm −2 (mass loading of 22 mg cm −2 ) at 1 A g −1, respectively, as well as outstanding rate performance. The resulting specific areal capacitance reaches an ultrahigh value of 7.91 F m −2 including a "self‐doping" defect contribution of 4.81 F m −2, which is dramatically higher than the theoretical capacitance of graphene (0.21 F m −2 ) and most of the reported carbon‐based materials. Therefore, the defect engineering route broadens the avenue to further improve the capacitive performance of carbon materials, especially for compact energy storage under limited surface areas. Abstract : Owing to the significantly improved double‐layer capacitance originating from the "self‐doping" defects, defective graphene blocks with high defect density ( I D / I G = 2.16), high packing density (0.917 g cm –3 ), and low specific surface area (29.7 m 2 g –1 ) show an integration of high gravimetric, volumetric, and areal capacitances for supercapacitors.